Papillon Flap—Design Modification of ALT Flap for Circumferential Laryngopharyngeal Defect - Singh, Sukhdeep; Brajesh, Vimalendu; Aggarwal, Aditya (Indian Journal of Plastic Surgery, 2023)
Anterolateral thigh (ALT) free flap is a commonly used flap for reconstruction of circumferential laryngopharyngeal defects. The flap is harvested as an ellipse and tubed along its length. We would like to present a design modification of the ALT flap where the tubing of the flap is done along the width of the flap. This design has advantages as it allows for a two-layered closure without the harvest of additional tissue and provides skin for neck coverage also. After inset, the flap resembles a butterfly, hence the name “Papillon Flap.”
Keywords: pharyngeal reconstruction; tubed anterolateral thigh (ALT) free flap; papillon flap